Profitability and marketing system of Binachinabadam-8 in some selected northern char areas of Bangladesh (Bangladesh Journal of Nuclear Agriculture, 2023)
The present study was undertaken to assess the profitability, marketing system, production and marketing problems of a groundnut variety, Binachinabadam-8 in the river bed areas of Rangpur, Gaibandha and Kurigram districts during 2022–23. The study analyzed the efficiency of different marketing chains by ranking performance indicators using a composite index formula. The average per hectare production cost of Binachinabadam-8 was Tk. 90,470 and the net return was Tk. 68,064. The benefit-cost ratio was estimated at 1.75 and 2.89 on a full cost and variable cost basis. The average estimated marketing cost was highest (Tk. 925/quintal) for Stockist and lowest (Tk. 87/quintal) for Arathdar. Net marketing margin was also highest (Tk. 1787/quintal) for Stockist and lowest (Tk. 115/quintal) for Arathdar. Farmer’s share in consumer prices of Binachinabadam-8 in different marketing chains was the highest in Chain-IV (65.46%) and the lowest was in Chain-I (63.98%). The performance indicators revealed that the Chain-IV was the most efficient of the chains. Farmers reported major problems including lack of irrigation facilities, high seed value, flood incidence, high fertilizer prices, lack of capital, lack of training and insect and pest. The farmers faced significant marketing challenges, including unstable prices, high transportation charges, lack of storage facilities and lack of cash capital. Therefore, the study will help to over undertake appropriate measures to overcome the production and marketing problems and thereby will increase the profitability and production of Binachinabadam-8 in the river bed areas of Bangladesh.Bangladesh J. Nuclear Agric, 37(2): 109-120, 2023